Landscape Dynamics and the Impact on Ecosystem Services Value Provided by Coastal Wetlands: An Update - Valdez, Vera Camacho; Ruiz-Luna, Arturo; Berlanga-Robles, César A. (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 4, 2023)
This study assessed the dynamics of land cover changes and the associated ecosystem services (ES) value of coastal wetlands in northwestern Mexico. Wetlands are ecosystems sensitive to changes in land use, affecting the supply and quality of the ES they offer, and are currently at risk due to the transformations promoted by economic activities (e.g. tourism, agriculture, aquaculture) to stimulate regional development. Remote sensing techniques were used to estimate change trends between 2000 and 2010, using the value transfer method for the economic valuation of ES and Markov chains to model probable scenarios for the years 2020, 2030 and 2050. Findings revealed that the ES total value flow for the period 2000-2010 tended to increase (18 million dollars (2007 USD)), with increasing estimates of high global value land covers, although locally they are of low value, as marsh/unconsolidated bottom, which increased in the estimated area during the study period. The most notable transition probability was observed among the natural wetlands, highlighting the littoral and the saltmarsh (unconsolidated bottom), as the classes with the highest probability of change over time. The southern region of the study area is the most susceptible to change, where unconsolidated bottoms and mangroves (forested saltmarsh) predominate.